Local interventions to prevent obesity in the WHO European region - a briefing review - Machado, Rita (2012)
Introduction: The increased prevalence of overweight and especially obesity affects the entire population in some countries regardless of age, sex and ethnicity, and has become a global public health problem. Following the WHO European Charter on counteracting Obesity and the EC White Paper “A strategy for Europe on Nutrition, overweight and Obesity related health issues”, highlighting the role of local authorities which have the great potential in creating the environments and opportunities for healthy living it was clear that action should be taken at both micro and macro levels and in different settings. Therefore, governments from the European countries have created, developed and implemented several obesity prevention interventions/programmes at national, regional and local levels. Objective: The aim of this review was to find and subsequently gather and interpret information regarding interventions/programmes at local or municipal level in the WHO European Region, which are intended to prevent overweight and/or obesity in children, adolescents, adults and elderly through the promotion of physical activity and change of food habits. Methodology: The search included scientific papers and grey literature. The scientific search engine was focused on PubMed, Medline and the World Health Organization, while grey literature was found using the Google browser. Results: From the 659 papers and websites found, 62 papers and websites (from 2006 to 2011) were included in this review comprising 23 interventions/programmes. 10 were community-based, 6 community- and school-based 6 school-based, and 1 family-based community interventions. Of the 23 interventions/programmes included, 17 related to both improving/changing nutrition habits and promotion of physical activity (73,9%); 5 related only to promotion of physical activity (21,7%); and 1 related only to the improve/change of nutrition habits (4,3%). Discussion: This brief review revealed that most of the interventions and programmes that promote physical activity, healthy food habits and environmental changes are effective at all levels (community, school and family) and may subsequently prevent and counteract overweight or obesity. Conclusions: Overall 60,8% of the programmes/interventions found proved to be effective and successful in preventing and/or reducing overweight and/or obesity and had improvement of food habits and physical activity levels on the target groups mentioned at the local or municipality level in the WHO European Region.